Metaphor of Animal in Balinese Pop Song - Candra Lestari, Ni Putu; Meilantari, Ni Luh Gede (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
In the lyrics of Balinese pop songs, metaphors are often found that use animal elements to describe characteristic of person either the feelings of the songwriter. The use of animal elements as a metaphor characterizes the author's point of view in expressing certain feelings. The songwriter's style to convey his feelings using self-made metaphors is one of the artistic values ??that builds the beauty of the song. This study aims to describe the use and meaning of metaphors that use animal elements. This can be analyzed by observing its literal meaning with its contextual meaning. This research is a qualitative descriptive study. The research sources are taken from several Balinese pop songs that are popular in the community. The meaning of metaphor is determined by looking at the relationship of certain lexical elements in the discourse. Metaphors containing animal elements found include ‘ buka cicing ngantosang segehan' , ‘ pesan amah cicing ', ‘ takut jak bojog ', and others. It can be concluded that songwriters use metaphors to describe feelings that cannot be expressed in ordinary words. The types of animal elements that are used as metaphors are animals that are commonly found in everyday life, making it easier for song listeners to understand the feelings conveyed by the songwriter.